Proteção de fontes de água em unidades de produção e vida familiares (UPVFS) no Sudoeste do Paraná: uma análise das ações desenvolvidas pela ACESI/STR, GETERR/UNIOESTE e EMATER-PR - Schimitz, Luiz Antonio (2017)
This research analyzes three projects of protection of springs / wells developed in the Southwest of Paraná by different institutions. For this purpose, 20 wells or wells were selected from the municipalities of Francisco Beltrão and Marmeleiro, considering the protections carried out, the characteristics of the surroundings and microbiological analyzes on water quality. In this dissertation, elements related to water and agricultural activities are discussed; Biological and chemical contamination of water; Diseases due to contact with it, insect ingestion and proliferation, and forms of pollution and water contamination. The problem of agricultural facilities and the inadequate disposal of human sewage in the contamination of springs is also highlighted. Regarding protection techniques, the main models used in the country and at the international level were discussed; The importance of maintaining cleaning, disinfection and the process of monitoring the microbiological quality of the source or protected well. In the experiences of the three projects, the objectives, established goals and techniques chosen by each project were analyzed, as well as the monitoring of water quality during project development. The UPVFs evaluated the maintenance status as well as the environmental situation of the spring environment through macroscopic analysis. In relation to protection techniques, three different types of protection techniques were identified: soil-cement system, spring protection box and vertical pipe, as well as three protections in shallow wells. In the diagnosis of the macroscopic parameters, two springs were classified in class "A" (optimal); Two in class "B" (good); Six in class "C", (reasonable); Three in class "D" (bad) and seven in class "E" (very bad). In this analysis it was detected that there are springs with good protection structures, while others need maintenance or reconstruction. The organoleptic water patterns were excellent in most cases. The location of the springs varies, so that there are protected sources in well preserved Permanent Preservation Areas (PPAs) or with little plant cover due to the existence of agricultural or livestock activities. In other cases, there are wells or wells near homes. In the microbiological analyzes, the results indicated that of the 20 analyzed points, with four samples of water collected by source or well, all the springs presented contaminations by total and thermotolerant coliforms, of which 15 had at least one sample with Escherichia coli contamination. Only five springs did not present this type of contamination. Of the 80 samples, only eight, from six sources, complied with Administrative Rule no. 2,914 / 2011 of the MS, being free of total coliforms and thermotolerant. The waters of the springs that presented the best microbiological quality are inserted in well preserved areas of APP or away from residence and agricultural facilities, or in sources where the farmer (a) performs periodic cleaning. It was concluded that there is a need to program urgent measures to improve the environmental situation of the sources that presented microbiological contaminations, ranging from improvements in protection, cleaning and disinfection, expansion of fenced areas and expansion of APP. In some more serious cases, it is suggested to change from the source to another more environmentally preserved.